Olefin metathesis in aqueous media - Tomasek, Jasmine; Schatz, Jürgen (Green Chemistry, 2013)
The worldwide undisputable and unattainable chemist is nature, using water as a solvent of choice in biosynthesis. Water as a solvent not only indicates "green chemistry" but is also inevitable in biochemical reactions as well as syntheses of several pharmaceutical products. In the last few decades, several organic reactions were successfully carried out under aqueous conditions, a powerful and attractive tool in organic synthesis metathesis reaction. This review summarises advances made in metathesis reaction in aqueous media. Two main strategies can be distinguished: the design of water soluble catalysts to obtain homogeneous conditions and using commercially available catalysts to utilize the advantages of heterogeneous conditions. © 2013 The Royal Society of Chemistry.